Vibrational features of graphene oxide powder nanocomposite coupled conical-cylindrical shells applicable for aerospace structures under various boundary conditions. (June 2023) - Sobhani, Emad; Safaei, Babak
Abstract: Overcoming the challenging circumstances encountered in aerospace components has led to the widespread use of small-scale reinforcements to improve structure-related performance. Accordingly, the vibrational properties of coupled conical-cylindrical shells (CCCSs) made of a matrix material reinforced by functionally graded graphene oxide powder (FGGOP) are numerically investigated under various boundary conditions (BCs) in this paper. To enhance the vibrational feature of the CCCS reinforced by graphene oxide powder (GOP), three models are measured regarding distribution related to this small-scaled material within the polymer along with the thickness related to the CCCS. The Halpin-Tsai homogenization form is also employed to develop the mechanical values associated with the GOP-nanocomposite materials. The main equations related to the CCCSs are obtained by joining Donnell's theory and the first shear deformation theory (FSDT). Additionally, using variation calculation (Hamilton's principle), the motion equations (MEs) of the CCCS reinforced by FGGOP are determined. Then, the generalized differential quadrature method (GDQM) is utilized to produce the system related to the MEs. Next, standard eigenvalue determination obtains the frequencies of the CCCS made of the FGGOP-nanocomposite. Finally, the frequencies of various benchmarks are compared with those determined here to validate the proposed scheme. Also, more than a few new and interesting samples are designed and solved numerically to indicate the impacts of the GOP, geometrical values, and various BCs on the vibration responses of the CCCS made of GOP-nanocomposite. Remarkably, this paper is the first evaluation related to the free vibration of the coupled conical-cylindrical shells reinforced by FGGOP under different BCs.